1998
DOI: 10.1046/j.1469-8137.1998.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene produced by the lichen Cladina stellaris exposed to sulphur and heavy‐metal‐containing solutions under acidic conditions

Abstract: Podetia of the terricolous lichen Cladina stellaris (Opiz) Brodo, collected in an unpolluted rural area in N. Finland, were wetted with either H # O, diluted acidic solutions of H # SO % , HNO $ and NaHSO $ , simulating acidic rain, or the following salts :The samples were further exposed to combined treatments in both acidic solutions, simulating acidic rain, and heavy metal salts in solution. Lichen samples wetted with H # O at pH 6n8, diluted solutions of H # SO % , HNO $ or a mixture of these two ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…The stress detected in the lichen is probably irreversible. The direct correlation of ethylene production and the Ba, Cu and Zn content of the lichen is comparable with findings of previous studies showing that both Cu and Zn increase the production of ethylene significantly in R. lacera at a low pH under laboratory conditions Garty 1991, Garty et al 1995a) and in Cladina stellaris (Kauppi et al 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The stress detected in the lichen is probably irreversible. The direct correlation of ethylene production and the Ba, Cu and Zn content of the lichen is comparable with findings of previous studies showing that both Cu and Zn increase the production of ethylene significantly in R. lacera at a low pH under laboratory conditions Garty 1991, Garty et al 1995a) and in Cladina stellaris (Kauppi et al 1998).…”
Section: Discussionsupporting
confidence: 91%
“…According to Schieleit (1996), the ethylene‐producing activity exists in axenic cultures of the mycobiont as well as in the photobiont and is obviously a metabolic product of the lichen thallus ( Schieleit and Ott 1996, 1997). Certain lichens produce elevated amounts of ethylene upon exposure to chemicals, especially FeCl 2 , under laboratory conditions ( Lurie and Garty 1991; Garty et al 1995a,b; Kauppi et al 1998). In the present work, an attempt was made to evaluate fluctuations in the production of ethylene, indicative of environmental stress, by transplanted lichens in biomonitoring sites.…”
Section: Introductionmentioning
confidence: 99%
“…At pH 2.0 the application of Fe 3π or Fe 2π combined with Clstimulated the release of ethylene by this lichen over and above the combination of Fe 3π and NO 3 or Fe 2π and SO 4 2- (Garty et al 1995). These results point to a synergistic effect of Fe 3π , Fe 2π and Cl - Controlled experiments revealed a high ethylene production in podetia of Cladonia stellaris exposed to FeCl 2 , relative to controls (Kauppi et al 1998). Field experiments showed that transplants of R. lacera produced high levels of ethylene in a Pb-contaminated road intersection relative to controls in a clean air site (Epstein et al 1986).…”
Section: Discussionmentioning
confidence: 83%
“…These results point to a synergistic effect of Fe 3+ , Fe 2+ and Cl – ions. Controlled experiments revealed a high ethylene production in podetia of Cladonia stellaris exposed to FeCl 2 , relative to controls (Kauppi et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos que avaliam a acumulação de elementos aerotransportados direcionados a líquens a partir de uma fonte de poluição específica também são comuns [9][10][11][12] . Há também estudos focalizados na retenção, localização, liberação, tolerância e toxicidade de diferentes elementos [13][14][15][16] . A morfologia do líquen influencia na taxa de acumulação dos elementos provenientes da atmosfera 17 .…”
unclassified